Exosomal circRNAs: Sorting Mechanisms, Roles and Clinical Applications in Tumors - Xu, Yanhua; Kong, Shan; Qin, Shiyi; Shen, Xianjuan; Ju, Shaoqing (Frontiers in Cell and Developmental Biology, 2020)
Exosomes are a group of nano-sized membrane vesicles and are important mediators of intercellular communication, particularly in tumor microenvironment. Recently, researchers have found that circular RNAs (circRNAs), with the great research significance, are enriched and stable in exosomes. In this review, we summarize the research significance of exosomal circRNAs, sorting mechanisms and their functioning mechanisms in tumor progression. Their clinical applications as clinical tumor biomarkers and as therapeutic targets in inhibiting tumor metastasis, anti-cancer immunity response and drug resistance have been widely discussed.